ANALISIS MANAJEMEN PENGELOLAAN KELAS DALAM MENINGKATKAN KEMAMPUAN KOMUNIKASI MULTILINGUAL DENGAN MODEL CONTEXTUAL TEACHING AND LEARNING - Qodri, Alviyatul; Maskud, Maskud; bin Madi, Faisol Nasar (STAI Ma'had Aly Al-Hikam Malang, 2024)
“The contextual teaching and learning model is Among several student management developed by combining classical learning by teaching staff at MTs Putri Nurul Huda Situbondo. The type of research used is qualitative research with a case study approach. The informants in this research were school principals, teachers, and students. Data collection techniques employed observation, interviews, and documentation studies. In this research, researchers used several stages of data analysis, namely the data condensation stage, data presentation stage, making temporary conclusions, and verification activities. The research results concluded that there are four stages of student management in improving multilingual communication competence: classroom layout management skills, time management skills and material coverage, and student management skills through language games. The CTL learning model is carried out in the planning stage, namely by making a learning implementation plan that refers to the independent curriculum, then the implementation stage, which contains three activity stages, namely preliminary activities, core activities, which contain the components of constructivism, inquiry, asking, learning community, modeling, reflection, then Closing activities use authentic assessment.